2006
DOI: 10.1021/ol0528991
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorophores with Rod-Shaped Polycyano π-Conjugated Structures:  Synthesis and Photophysical Properties

Abstract: [reaction: see text] Novel rod-shaped polycyano-oligo(phenyleneethynylene)s were synthesized by Pd cross-coupling reaction. Polycyano groups were found to greatly improve the emission efficiency (Phi(f)) of OPEs. By the end donor modification, we achieved the creation of very intense blue light-emitting fluorophore with the SMe group (Phi(f) = 0.972, log epsilon 4.89, lambda(em) 455 nm) and very intense yellow light-emitting fluorophore with the NMe(2) group (Phi(f) = 0.999, log epsilon 4.75, lambda(em) 555 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 8 publications
3
33
0
Order By: Relevance
“…Consequently, a linear relationship is again obtained between the F F and s p + values in the solid state, as shown in Figure 8, which affords Equation (8). Although a similar linear relationship between the F F and s p values has been reported for other oligo(phenyleneethynylene) derivatives in solution, [24] such a relationship in a solid-state emission is unprecedented to the best of our knowledge. In a comparison of Equations (3) and (8), the higher intercept value with the smaller slope constant in Equation (8) demonstrates a trend that the value for F F in the solid state becomes higher than those in solution.…”
Section: Dnsupporting
confidence: 71%
“…Consequently, a linear relationship is again obtained between the F F and s p + values in the solid state, as shown in Figure 8, which affords Equation (8). Although a similar linear relationship between the F F and s p values has been reported for other oligo(phenyleneethynylene) derivatives in solution, [24] such a relationship in a solid-state emission is unprecedented to the best of our knowledge. In a comparison of Equations (3) and (8), the higher intercept value with the smaller slope constant in Equation (8) demonstrates a trend that the value for F F in the solid state becomes higher than those in solution.…”
Section: Dnsupporting
confidence: 71%
“…74−85 Furthermore, it has been found that donor/acceptor modification shown in structure A is superior to that shown in structure B for emission in the visible region ( Figure 4). 86,87 On the basis of these results (the effectiveness of donor/ acceptor tuning, Figure 3) and the superiority of tuning mode A (see Figure 4), 20 compounds (D/A-BPBs: Type I, Type II, Type III, Type IV, and Type V) were designed as shown in Figure 5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In fact, several oligomers of ethynylene-extended arenes and heteroarenes have been designed and synthesised. [16][17][18][19][20][21] It has been shown that they function as nanoscale "molecular wires", with the extent of intramolecular conjugation dependent on the topology of the p system and the molecular length. [22][23][24] It is well known that both fluorene and anthracene are blue fluorophores whose derivatives have been widely used as emitting materials; in fact, some poly(fluorene-co-anthracene)s with controlled alternative fluorene and anthracene structures have been reported.…”
Section: Introductionmentioning
confidence: 99%